2014
DOI: 10.1093/jhuman/huu011
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, Encounters and Expectations: The Uncertain Ethics of 'The Field'

Abstract: Entering 'the field' can be a daunting, demanding and at times bewildering experience, with researchers negotiating a myriad of assumptions, expectations and motivations. Whilst early career researchers and doctoral students may be trained in theories of research practice, research design and ethical conduct, the realities of actually doing research often test the limits of such formal training and knowledge. In this practice note, I draw upon my experience of fieldwork in the UK working with dispersed asylum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 19 publications
(17 reference statements)
1
21
0
2
Order By: Relevance
“…However, I was cautious about smiling at the females if they did not already know me as I was aware it might be culturally offensive. In this context, I recalled several researchers' experiences (Brown, 2009;Darling, 2014;Okumus et al, 2007;Riaz, 2013;Widding, 2012) that suggested the need to exercise flexibility and reflexivity while entering the research field. For example, Subedi (2006) completed high school in Nepal and studied higher education in the USA but also experienced the need to re-negotiate the basis of the interaction between researcher and participants when entering the field in Nepal.…”
Section: Cultural Differences and Language Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, I was cautious about smiling at the females if they did not already know me as I was aware it might be culturally offensive. In this context, I recalled several researchers' experiences (Brown, 2009;Darling, 2014;Okumus et al, 2007;Riaz, 2013;Widding, 2012) that suggested the need to exercise flexibility and reflexivity while entering the research field. For example, Subedi (2006) completed high school in Nepal and studied higher education in the USA but also experienced the need to re-negotiate the basis of the interaction between researcher and participants when entering the field in Nepal.…”
Section: Cultural Differences and Language Barriersmentioning
confidence: 99%
“…As such, I look forward to this project as both an exciting and challenging stage of the entire research, supported by the three other named authors. Darling (2014) stated that entering the field can be a daunting and bewildering experience where researchers may have to adjust and compromise with many assumptions and expectations. I noted that entry into fieldwork is often an early and harsh test of the research design and ethical demeanour that doctoral students have been theoretically trained to practice.…”
Section: Introductionmentioning
confidence: 99%
“…The study of social trauma and vulnerable groups can have emotional repercussions on the participants, researchers and the readers alike (Darling, 2014;Hugman et al, 2011;Refugee Studies Center, 2007), particularly when they belong to conflicting social groups (Chaitin, 2003).…”
Section: Reflexivitymentioning
confidence: 99%
“…Gallo, 2009 (Darling, 2014) und zum anderen ein Zugeständnis punkto Unwissenheit innerhalb der Feldforschung ermöglichen (vgl. England, 1994).…”
Section: S Finger: Carpe Noctem: Forschen Auf Dem Strichunclassified